A study of the production system of Miracle Candle Cottage Industries - Leyble, Edmundo (College of Engineering, 2002)
Miracle Candle Cottage Industries is a leading manufacturing company that produces made-to-stock and made-to-order candles. With the tools and techniques learned in the Production and Operations Management course, the group was able to identify and resolve four major problems in the production system of the company. The first major problem identified is the Inefficient Plant Layout. the group recommends the company to modify the existing plant layout and align it with the company's competitive priorities. The second major problem identified is the Insufficient Forecasting Methods. The group recommends the company to use as quantitative forecasting method either the Simple Moving Average with N=9 or the Weighted Moving Average with N=6 and weights of 0.5, 0.3, and 0.2. The third major problems identified is the Poor Aggregate Planning. The group recommends the company to apply Periodic Review Systems with review intervals of 26 days for the paraffin wax and 78 days for the wick. THe implementation of the proposals would improve the production system of the company with regards to a higher efficiency, lower costs, and better quality. By aligning with its competitive priorities, Miracle Candle Cottage Industries could fulfill to its strategies.